2019
DOI: 10.1017/s1092852919001457
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of trial-based cognitive therapy, behavioral activation and treatment as usual in the treatment of major depressive disorder: preliminary findings from a randomized clinical trial

Abstract: Introduction. Major depressive disorder (MDD) is a prevalent, debilitating and disabling disorder, and its prevalence is increasing. Antidepressants (AD), cognitive-behavioral therapy (CBT) and behavioral activation (BA) are the main treatments for MDD. Trial-based cognitive therapy (TBCT) addresses and restructures dysfunctional negative core beliefs (CBs) and is a novel and promising approach. Objective. The aim of this study was to compare the efficacy of TBCT, BA and treatment as usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 68 publications
0
12
0
2
Order By: Relevance
“…All patients included were using stable doses of AD. We conducted a secondary analysis 51 of suicidality variables from a published 44 and registered clinical trial (clinicaltrials.gov: NCT02624102). The Institute of Health Sciences ethics committee at the Federal University of Bahia approved this study (CAAE: 44663315.4.0000.5662).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients included were using stable doses of AD. We conducted a secondary analysis 51 of suicidality variables from a published 44 and registered clinical trial (clinicaltrials.gov: NCT02624102). The Institute of Health Sciences ethics committee at the Federal University of Bahia approved this study (CAAE: 44663315.4.0000.5662).…”
Section: Methodsmentioning
confidence: 99%
“…The original database 44 was evaluated and tabulated with the Software Package for Social Sciences, version 24 61 . For this study, descriptive statistics for gender, marital status, dropout rate, means and standard deviations of the scales and the primary measures were performed.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that patients with comorbid SMI and chronic diseases may not enjoy a high quality of life unless internalized stigma is eliminated, which would then lead to higher levels of patient activation. As shown in previous studies, patient activation interventions have been successful in improving emotional, cognitive, and behavioural symptom management in patients with SMI (Hemanny et al., 2019; Muralidharan et al., 2019). A previous meta‐analysis also indicated that the involvement of patients with chronic diseases in managing their own care significantly improved their physiological, psychosocial, and behavioural health outcomes (Lin et al., 2020).…”
Section: Discussionmentioning
confidence: 65%
“…TBCT is a transdiagnostic approach, 57 whereas PE was designed as a particular exposure-based treatment protocol to treat PTSD. 58 Considering that TBCT has been demonstrated to be effective for depression 18 and SAD, [19][20][21][22] it may be considered an option for treating patients with PTSD and comorbid conditions, such as depression and SAD. The study by Caetano et al 20 included SAD patients with high rates of comorbid disorders, especially depression, and demonstrated that participants in the TBCT group had significantly decreased social anxiety, social avoidance, and depressive symptoms, whereas no differences were observed between pretreatment and posttreatment measures in the waitlist condition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, assuming that PE changes the belief that a person cannot handle thinking about the trauma, whereas CPT is more likely to change beliefs related to self-blame, then it may be possible to select the individual's profile of beliefs to maximize treatment benefit. 16 Trial-based cognitive therapy (TBCT) 17 is a novel transdiagnostic approach effective in depression 18 and social anxiety disorder (SAD). [19][20][21][22] Although TBCT restructures cognition in a similar fashion as conventional CBT and CPT, TBCT is distinctive in that it introduces a new, organized, and systematic approach to modify dysfunctional core beliefs by presenting an easy-to-remember caseformulation model while allowing cognitive, emotional, and experiential work to be implemented simultaneously.…”
Section: Introductionmentioning
confidence: 99%